Politically-focused intrusive thoughts and associated ritualistic behaviors in a community sample. (May 2018) - Cepeda, Sandra L.; McKay, Dean; Schneider, Sophie C.; La Buissonnière-Ariza, Valérie; Egberts, Jolenthe T.N.E.; McIngvale, Elizabeth; Goodman, Wayne K.; Storch, Eric A.
Highlights: Politically-focused intrusive thoughts and ritualistic behaviors (PITRB) occurred frequently. 25.2% reported experiencing at least one PITRB multiple times a day. PITRB was associated with all measures of psychopathology and disability. Anxiety control moderated the relationship between PITRB and both anxiety and depression. Abstract: A significant proportion of the U.S. population report increased stress attributed to the political climate following the controversial 2016 United States (U.S.) Presidential election. The political stressors paired with the growth in news consumption and social media-use could be a potential trigger for obsessive-compulsive-like symptoms specific to politics in some individuals. This study aimed to elucidate the rate of Politically-focused Intrusive Thoughts and associated Ritualistic Behaviors (PITRB), their demographic and clinical correlates, and the degree of association with political ideology. Survey data were collected using the crowdsourcing platform Mechanical Turk. A total of N = 484 individuals completed the survey. Measures of politically-focused intrusive thoughts and ritualistic behaviors, general obsessive-compulsive symptoms, depression, anxiety, anxiety control, worry, and disability were administered, as well as a measure of social and economic conservative affiliation. Results showed that a quarter of the sample (25.2%) had at least one PITRB more than once a day. PITRB was associated with all measures of psychopathology and disability. Finally, anxiety control moderated the relationship between PITRB and both anxiety and depression. No differences in psychopathology were found between major party affiliations. The findings suggest that politically-focused intrusive thoughts and ritualistic behaviors are associated with psychopathology domains in a manner comparable to general obsessive-compulsive symptoms.